2009
DOI: 10.1088/0026-1394/47/1/007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different vibration exciter systems on high frequency primary calibration of single-ended accelerometers

Abstract: During the monitoring of the long term stability of two accelerometers intended for use in the CIPM Key Comparison CCAUV.V-K2, significant deviations of the magnitude results of the single-ended transducer were discovered. These deviations depend on whether the calibration was performed on an armature made of beryllium or of ceramic. Further investigations showed that this effect must be attributed to some not yet readily understood dynamic process between the contact surfaces of the accelerometer and the arma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…As with all primary accelerometer calibrations, [38][39][40][41][42] there are many parasitic dynamic effects that can lead to systematic errors. For instance, we found that it was important to consider non-rigid body motion of the accelerometer package.…”
Section: A Harmonic Vibration Testingmentioning
confidence: 99%
“…As with all primary accelerometer calibrations, [38][39][40][41][42] there are many parasitic dynamic effects that can lead to systematic errors. For instance, we found that it was important to consider non-rigid body motion of the accelerometer package.…”
Section: A Harmonic Vibration Testingmentioning
confidence: 99%
“…Bruns et al [5] have reported the comparison of charge sensitivity results of a single-ended (SE) accelerometer B&K 8305-001 on two different vibration exciters: a PTB modified version of the Bouche shaker (VE) and a SPEKTRA SE-09 shaker. The results obtained exhibited a systematic deviation which increased with rising frequency, starting at 5 kHz.…”
Section: Dispersion Observed In Different Excitersmentioning
confidence: 99%
“…This has been reported by Dr. Thomas Bruns in 2009, during the IMEKO TC 22 technical meeting in Lisbon. Later on, two articles related to this problem were published in Metrologia [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Les écarts constatés entre les étalonnages menés dans les deux configurations sont inférieurs à la somme Des écarts de l'ordre de 1 % à 10 kHz entre des étalonnages réalisés avec deux excitateurs de conception et de matériau différents ont déjà été observés par d'autres [5]. Ils ont également été constatés entre des éta-lonnages réalisés avec des raccords différents [6].…”
Section: Comparaison Avant Et Après Le Changement D'excitateurunclassified